Pitfall management of dermatofibrosarcoma protuberans on right leg - Winarta, Gede Kesuma; Suryawisesa, Ida Bagus Made (International Journal of Research in Medical Sciences, 2019)
Dermatofibrosarcoma protuberans (DFSP) is a rare, locally invasive soft tissue sarcoma. The local recurrence rate is high, in some studies upwards of 60%, likely reflecting a failure to remove occult extensions of tumor. Surgical excision has been the treatment of choice for the resection of DFSP. Any pitfall on management therapy of DFSP not only increase the recurrence rate but also add new problems to patients with DFSP. 58-year-old male patient, came with a local recurrent of DFSP on his right leg. Then performed excision with margin one centimetre, and closing defect using pedicle sural flap, durante surgery turned pedicle on the flap is too short and because of poor soft tissue handling pedicle was injured. It consulted into the vascular division for evaluated and treatment pedicle. Postoperative evaluation, the flap experiences bluish due to vascularization compromised. It was decided to expose the flap and the defect was covered with skin graft. 2 months postoperative evaluation found local recurrent on skin graft area. Excision margins between 2 to 5 cm can reduce the recurrence rate. Proper planning in designing flaps to cover defects and the ability of good soft tissue handling is required to avoid new problems on management DFSP.